Gastrointestinal stromal tumors: Treatment patterns of a population‐based sample. Issue 6 (May 2015) - Harlan, Linda C.; Eisenstein, Jana; Russell, Maria C.; Stevens, Jennifer L.; Cardona, Kenneth
Abstract : Objectives: The National Cancer Institute (NCI) annually confirms therapy with treating physicians on a sample of patients diagnosed with a specific cancer. Methods: Using the NCI Patterns of Care data, treatment patterns were examined on a population‐based sample of patients diagnosed with gastrointestinal stromal tumors (GIST) in 2008. Results: A random sample of 323 of 405 GIST patients registered in SEER was selected. Most patients had gastric GISTs, were ≥65 years, white, had private insurance, and treated in a hospital with a residency program. Surgery was primarily performed in patients with non‐metastatic disease (94%), in which: 26, 12, and 36% were at low, intermediate, and high‐risk of recurrence, respectively. Amongst low‐risk patients, ∼30% received adjuvant therapy. Amongst patients at higher risk, 26–40% did not receive adjuvant therapy. Imatinib was the most common targeted therapy administered. On multivariate analysis, age and risk‐group were associated with receipt of adjuvant targeted therapy. Conclusions: Our study shows that in 2008, the majority of patients diagnosed with GIST received appropriate surgical and adjuvant therapies. However, a considerable subset may have been overtreated and undertreated. Future studies identifying factors that impact the delivery of adjuvant therapy should be conducted. J. Surg. Oncol. 2015 111:702–707 . © 2015 Wiley Periodicals, Inc.